Exogenous sex steroid hormones and asthma in females: protocol for a population-based retrospective cohort study using a UK primary care database. Issue 6 (27th June 2018) - Nwaru, Bright I; Simpson, Colin R; Soyiri, Ireneous N; Pillinger, Rebecca; Appiagyei, Francis; Ryan, Dermot; Critchley, Hilary; Price, David B; Hawrylowicz, Catherine M; Sheikh, Aziz
Abstract : Introduction: Female sex steroid hormones have been implicated in sex-related differences in the development and clinical outcomes of asthma. The role of exogenous sex steroids, however, remains unclear. Our recent systematic review highlighted the lack of high-quality population-based studies investigating this subject. We aim to investigate whether the use of hormonal contraception and hormone replacement therapy (HRT), subtypes and route of administration are associated with asthma onset and clinical outcomes in reproductive age and perimenopausal/postmenopausal females. Methods and analysis: Using the Optimum Patient Care Research Database (OPCRD), a national primary care database in the UK, we will construct a retrospective longitudinal cohort of reproductive age (16–45 years) and perimenopausal/postmenopausal (46–70 years) females. We will estimate the risk of new-onset asthma using Cox regression and multilevel modelling for repeated asthma outcomes, such as asthma attacks. We will adjust for confounding factors in all analyses. We will evaluate interactions between the use of exogenous sex hormones and body mass index and smoking by calculating the relative excess risk due to interaction and the attributable proportion due to interaction. With 90% power, we need 23 700 reproductive age females to detect a 20% reduction (risk ratio 0.8) in asthma attacks for use of any hormonal contraception and 6000 perimenopausal/postmenopausal females to detect a 40% (risk ratio 1.40) increased risk of asthma attacks for use of any HRT. Ethics and dissemination: We have obtained approval (ADEPT1317) from the Anonymised Data Ethics and Protocol Transparency Committee which grants project-specific ethics approvals for the use of OPCRD data. Optimum Patient Care has an existing NHS Health Research Authority ethics approval for the use of OPCRD data for research (15/EM/150). We will present our findings at national and international scientific meetings and publish the results in international peer-reviewed journals. Trial registration number: EUPAS22967.